THE ROLE OF FELLOWSHIP IN BUILDING RELATIONSHIPS AMONG CONGREGATION MEMBERS AT GMIM FILADELVIA WOWONTULAP: Peran Persekutuan Dalam Membangun Hubungan Antarwarga Jemaat Di GMIM Filadelvia Wowontulap - Vicky Maisa; Alfio Tamaweol; Jonathan Tumangkeng; William Goni; Deron Binilang; Mieke Nova Sendow; Linda Patricia Ratag; Evi Stans Evlin Tumiwa (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Abstract Ecclesial fellowship in GMIM Filadelfia Wawontulap has ceased being a ritualized liturgy to a crucial place of creating genuine relationships, solving conflicts, and the assimilation of Biblical values and Minahasan culture. Through descriptive-interpretative qualitative research approach, the study analyzes the role of fellowship as a merging and healing process among church members and uses five themes namely, the strengthening of social-spiritual relationships, the church as a reconciler, the leadership of pastors and elders, the integration of mapalus in koinonia, and the means of increasing participation and belonging. Results indicate that social bonding among fellowship activities at the column, commission, and categorical levels, generational relational gaps, and helpful mutual support between generations, be it at the hospital visit or a common meal. The church plays an active role in mediating conflicts in an all-inclusive pastoral ministry which involves prayer, open dialogue, and personal accompaniment. Although pastors and elders are appreciated as spiritual advisors, members want more personal contact and less formality to help bring openness, particularly among young people and those who are shy. The Minahasan cultural ethics, especially of mapalus (mutual cooperation), are highly effective social capital, and support equality, solidarity, and togetherness, which is similar to New Testament koinonia. Some of the best approaches to promote participation are informal intergenerational events, youth participation with planning the events, frequent visits to the aged and non-judgmental area where the youth can share their personal plight.